Influence and Strategy Research of Cross-Regional Renewable Energy Incremental Spot Trading. (June 2018) - Hua, Mao; Yuanyuan, Li; Kui, Wang; Dawei, Yan; Zheng, Lei; Jin, Zhou
Abstract: Due to the incremental spot trading position for sending provinces of abandoned energy(water, wind or photovaltic power), the renewable energy increment spot transaction has obvious price advantages. At present, grid enterprises should actively participate in the spot trading of renewable energy in inter-regional provinces. With the reform of the electric power system, the power grid enterprises can participate in the spot trading of renewable energy of renewable energy in the inter-regional provinces through their own sales companies. By purchasing the peak support service from the power plant, we should deal with the peak problem caused by the spot trading of renewable energy in trans-regional provinces. The resulting peak support service costs are no longer shared by power plants, but should be compensated for by the profit generated by the incremental spot exchange.